Nurses and Medical Physics: an observational study on the knowledge of the physical basis of Medical Devices. - Ilaria Stura; Caterina Guiot (Università degli Studi di Torino, 2023)
BACKGROUND In recent decades, nursing is increasingly considered as a scientific discipline. Subjects such as Medical Physics, Statistics, and scientific method are important in professional training. In particular, understanding the physical basis of medical devices, their elaborated parameters, the methods and how information reaches the nurse allows a more informed practice. OBJECTIVES Primary objective. Investigate nurses' knowledge of the physical basis of the used medical device. Secondary objective. Investigate whether the qualification type (professional school, diploma, or degree), the years since the end of the study, age, or Italian regional origin can influence this knowledge. METHODOLOGY An observational study was conducted using an anonymous online questionnaire developed ad hoc and addressed to nurses working in Italy. The responses were analyzed with chi-square tests divided by type of studies, years since the end of the study, and Italian region of origin. RESULTS More than half of the interviewees were unable to give the correct answer on the functioning of the sphygmomanometer (54.3%) and phonendoscope (53.0%). ECG and oximeter are the most understood instruments (79.0 and 67.9% correct answers respectively). 45.7% of interviewed do not remember that one cubic centimeter (CC) and one milliliter (ml) have a conversion factor of 1. No differences were found by qualification type, years since the end of the study (considering both the median and a limit of 5 years for new graduates), age, and Italian region of work (p>0.05). DISCUSSION and CONCLUSIONS Knowledge of the physical basis of the used medical devices does not seem to degrade over time.  In the light of this, it would be more useful to consolidate these foundations in the three-year degree course of Nursing, rather than investing in post qualification courses. Such training, however, would be desirable to allow current professionals to fill the gaps emerged in this study.